Clinical Efficacy of the 940-nm Diode Laser in the Treatment of Recurrent Pockets in the Periodontal Maintenance Phase: 940-nm Diode Laser Effect on Recurrent Periodontal Pockets - Alizadeh Tabari , Zahra; Pournasir , Leila; Mohammadreza, Sadegh; Anbari, Fahimeh (Journal of Lasers in Medical Sciences, 2021)
Introduction: The basis of periodontal treatments is the mechanical removal of bacterial biofilm, which is often not sufficient. Therefore, laser therapy can be effective as an adjunct treatment. The aim of the present study was to evaluate the clinical efficacy of the 940-nm diode laser in the treatment of recurrent pockets of patients in the periodontal maintenance phase. Methods: The present clinical trial study was performed on 20 patients. Clinical indices, including bleeding index (BI), probing pocket depth (PPD), and clinical attachment level (CAL) of the studied teeth were recorded before the test. The different quadrants were randomly divided into two experimental (scaling and root planing (SRP)+Laser) and control groups (SRP alone). Both groups were matched in terms of plaque index (PI). Clinical indices were re-recorded using therapeutic methods 30 and 90 days after the treatment and data analysis was carried out using the t-test and LSD. Results: There were no significant differences in PI, PPD, CAL, and BI in both groups before the treatment (P>0.05). However, there were significant differences in PPD, CAL, and BI in the two groups one month after the treatment (P<0.05); it means that improvements were more significant in the experimental group than in the control group. Comparing experimental and control groups, we found that there were no significant differences in PPD and CAL indices three months after the treatment (P>0.05); however, there were significant improvements in the BI index in both groups (P<0.05), so that the improvement was better in the experimental group than the control group. Conclusion: Both SRP+Laser and SRP alone improved clinical indices in patients. In short-term follow-up, the effect of SRP+Laser treatment on BI, CAL, PPD was significantly superior to SRP treatment alone, but in long-term follow-up, SRP+laser was more effective than SRP alone in improving the BI index. DOI:10.34172/jlms.2021.68